Hidden in Plain Sight: How to Find and Execute Your Company's Next Big Growth Strategy - Douglas Kimberly (Wiley, 2009)
Companies must innovate to grow, but they often forget to look beyond their own brands. Take Sony, for example. Its success with consumer innovations like the Walkman blinded it to obvious changes in how, when, and where people wanted their music. Apple capitalized on those changes in demand with the iPod, providing a new way of listening to music and of managing one’s entire music library.